IMMEDIATE AND LATE EFFECT OF CRYOTHERAPY ON BALANCE IN HEALTHY SUBJECTS (International Journal of Physiotherapy, 2017)
Background: cryotherapy application is commonly used as a physical therapy tools with many advantages, however numerous researchers have stated decrease in subject balance which affects quality of movement following cryotherapy application, thus the purpose of study was to investigate the immediate and late effect of cryotherapy on ankle dominant joint on static balance and test the difference in static balance change between both sexes.Methods: Thirty healthy subjects, Subjects had their static balance tested during two conditions: (1) an experimental condition where the subject received the cryotherapy application by using cooled gel pack to the dominant ankle joint for 15 minutes immediately before static balance testing and (2) a control condition finished at room temperature. Using coin flip for randomization the order of examining condition. Biodex balance system was used to measure static balance.Results: analysis of data using ANOVA and unpaired test, show insignificantly statistically effect in all aspect of static balance within female group and within male group with p-value of overall stability index for female=0.669, for male =0.382, Anterior/posterior stability index for female =0.196, for male=0.552 and medial/lateral stability index for female =0.989, for male=0.46 and insignificant statistically difference between male and female in all aspect of static balance.Conclusion: the result of the study suggest that using cold gel pack for fifteen minutes of cold gel pack on dominant ankle extremity have no effect on static balance on both sexes.